CLEC4M overexpression inhibits progression and is associated with a favorable prognosis in hepatocellular carcinoma - Yu, Qianle (Mol Med Rep, 2020)
Hepatocellular carcinoma (HCC) remains the most common malignant cancer worldwide. Numerous studies have indicated that C-type lectin domain family 4 member M (CLEC4M) is associated with tumor progression; however, the biological functions of CLEC4M in HCC have not been investigated. In the present study, CLEC4M overexpression was observed to be associated with a favorable patient overall, relapse-free, progression-free and disease-specific survival by using the KMplot™ database. The present study then concentrated specifically on the functions of CLEC4M by performing cell counting kit-8 proliferation, 5-Ethynyl-2′-deoxyuridine and flow cytometric assays. CLEC4M overexpression inhibited proliferation and enhanced apoptosis in Huh7 and PLC/PRF/5 cells. Furthermore, the results demonstrated by using western blotting that CLEC4M overexpression inhibited the Janus kinase 1/signal transducer and activator of transcription 3 pathway, which is involved in various types of tumors including HCC. In conclusion, the present study reported that CLEC4M may be considered as a novel indicator of HCC and may provide a theoretical basis for improving the survival of patients with HCC.